Faktor Anteseden yang Mempengaruhi Brand Trust dan Brand Loyalty pada Restoran Fastfood di Indonesia - Hartono, Anggito; Cahyono, Roby; Arafah, Willy (BUDGETING : Journal of Business, Management and Accounting, 2024)
The research findings and discussions indicate that advertising and social network service content have a positive impact on customer engagement and brand trust. Additionally, customer engagement also positively influences brand trust and brand loyalty. Thus, advertising, social network service content, and customer engagement are important precursor factors in building brand trust, which in turn affects brand loyalty. This highlights the importance of addressing and managing these aspects in marketing strategies to achieve long-term goals in building and maintaining customer loyalty. Keywords: Antecedent Factors, Brand Trust and Brand Loyalty of Fast Food Restaurants.